ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Husain, Mark; Prihatiningtya, Nindy Citroresmi; Buyung, Buyung (Universitas Islam Sumatera Utara, 2024)
This research aims to: 1). Describe how students' mathematical reflective thinking abilities with high learning independence on SPLDV material. 2) Describe how students think reflectively mathematically with moderate learning independence on SPLDV material. 3) Describe how students with low learning independence use reflective mathematical thinking in SPLDV material. This research method is descriptive research (Description Research) and the approach used is a qualitative approach. The subjects in this research were students in class VIII C at SMPN 17 Singkawang. The instruments used in this research were a learning independence questionnaire and a mathematical reflective thinking ability test. From the research results it can be seen that; (1) with high learning independence, students are able to work on indicator questions for the Reacting, Elaborating and Contemplating phases; (2) in moderate learning independence, students are able to work on questions in the Reacting and Elaborating phases, but students are not yet able to work on indicator questions in the Contemplating phase with correct results; (3) with low learning independence, students are unable to work on questions on the Elaborating and Contemplating phase indicators with correct solutions and results, but students are able to work on questions on the Reacting phase indicators correctly. Based on the results of the analysis it can be concluded that; (a) Mathematical reflective thinking ability with high learning independence is in the high category; (b) Mathematical reflective thinking ability with moderate learning independence is in the low category, and; (c) Mathematical reflective thinking ability with low learning independence is in the low category.